Transcranial Electric Current Stimulation During Associative Memory Encoding: Comparing tACS and tDCS Effects in Healthy Aging - Klink, Katharina; Peter, Jessica; Wyss, Patric; Klöppel, Stefan (Frontiers in Aging Neuroscience, 2020)
Associative memory is one of the first cognitive functions negatively affected by healthy and pathological aging processes. Non-invasive brain stimulation techniques are easily administrable tools to support memory. However, the optimal stimulation parameters inducing a reliable positive effect on older adult’s memory performance remain mostly unclear. In our randomized, double-blind, cross-over study, 28 healthy older adults (16 females; 71.18 + 6.42 years of age) received anodal transcranial direct (tDCS), alternating current in the theta range (tACS), and sham stimulation over the left ventrolateral prefrontal cortex each once during encoding. We tested associative memory performance with cued recall and recognition tasks after a retention period and again on the following day. Overall, neither tDCS nor tACS showed effects on associative memory performance. Further analysis revealed a significant difference for performance on the cued recall task under tACS compared to sham when accounting for age. Our results suggest that tACS might be more effective to improve associative memory performance than tDCS in higher aged samples.